Lyapunov method: a tool to describe fabric attractor in non-linear and heterogeneous flows with application to shear zones - Iacopini, D.; Carosi, R. (TRABAJOS DE GEOLOGÍA, 2009)
In this contribution we review and expand the concept of attractor to non-linear flow system, introducing the concept of stability analysis to unravel some simple heterogeneous flow system. A semi-quantitative tool (using Lyapunov method) is suggested to predict the fabric attractor within some simple and general shear zones defined by non-linear flow tensor. The theory is briefly explained and it is shown the potentiality of this approach on describing the flow in heterogeneous shear zones. An example is discussed and a kinematic classification of some possible non-linear flow systems, using Lyapunov exponent analysis, is proposed.